Peran Mahasiswa Dalam Mendukung Pelayanan Masyarakat Di Kantor Desa Dusun Baru Kecamatan Ilir Talo - Trisna, Rama Dita; Hanila, Siti; Fitriano, Yun; Agung, Kimas Kurniawan Tando; Prawitasari, Andriyani; Herlina, Yeni; Effendi, Bahman (Jurnal Dehasen Untuk Negeri, 2025)
The village government serves as the frontline in delivering public services in Indonesia, particularly in providing administrative services to the community. However, challenges such as limited human resources and technology often hinder the effectiveness of these services. The Field Work Practice (PKL) activity conducted by students at the Dusun Baru Village Office, Ilir Talo Sub-district, aims to support the implementation of public services, especially in managing administrative letters and handling community complaints. The PKL activities included observation, active participation in administrative services, and assisting community members. The results showed that student involvement was able to improve the efficiency and accuracy of service processes, as well as provide innovative solutions to technical challenges in the field. Therefore, the role of students has proven to be strategic in helping village officials deliver more responsive and professional services.